The effect of a digital health coaching and health education protocol on cognition in adults at-risk for Alzheimer’s - Anthony Campitelli; Joshua L. Gills; Megan D. Jones; Sally Paulson; Jennifer Myers; Kelsey Bryk; Erica N. Madero; Jordan M. Glenn; Charlie H. Rodgers; Jenova A. Kempkes; Michelle Gray (GeroScience, 2023)
Several modifiable lifestyle factors have been linked to cognitive ability and the risk of developing Alzheimer’s disease and related dementias (ADRD). Health coaching (HC) is an intervention that addresses lifestyle factors associated with cognition. The effectiveness of an HC protocol was evaluated and compared with a health education (HE) intervention, representing the current standard of care, in a sample of 216 adults between the ages of 45 and 75 years who were at-risk for developing ADRD. Outcomes examined were global cognition, neuropsychological cognition, and Alzheimer’s risk. HC participants received personalized coaching from a health coach focusing on nutrition, physical activity, sleep, stress, social engagement, and cognitive activity. HE participants received biweekly education materials focusing on the same modifiable lifestyle factors addressed by HC. Participants were assessed at baseline and again 4 months later. Self-reported global cognition scores improved only in the HC group (16.18 to 15.52, p = .03) and neuropsychological cognitive ability improved in the HE group (104.48 to 108.76, p < .001). When non-adherence in the HC group was accounted for, however, the mean change in neuropsychological score was similar between groups ( p > .05), self-reported global cognition demonstrated an even larger mean improvement in the HC group (16.20 to 15.41, p = .01), and the HC group saw an improvement in ADRD protective risk score (− 10.39 to − 11.45, p = .007). These results indicate that HC and HE can both improve cognition, but HC may be more effective and may yield increased protection against ADRD risk.